Implementation of Islamic Bank Mudharabah Financing in Makassar - Nurdin, Maryam; Mukhtar Lutfi; Muhammad Wahyuddin Abdullah; Saiful Muchlis (SENTRALISASI, 2024)
This study aims to determine the implementation of mudharabah contracts in Islamic banks. The type of research used is qualitative. This research was conducted with in-depth interviews. The informants who will be the source of data in this research are people who are directly involved in mudharabah financing practices. Informants were determined by purposive sampling and snowball techniques. Informants were determined by certain criteria: (1) Islamic banking leaders in Makassar (2) Islamic banking account officers in Makassar (3) Customers who are or have received mudharabah financing. The total number of informants is 5 people. The results showed that there is a high risk of moral hazard so that this financing is transferred to the Mudharabah contract, so the conclusion of this study is that the implementation of the mudharabah contract is not fully implemented.